2015
DOI: 10.1108/mip-05-2014-0081
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumers’ attitudes and purchase intentions of e-deals

Abstract: Purpose – The purpose of this paper is to identify the key antecedents of attitude towards electronic deals (e-deals) and factors influencing purchase intention of e-deals. Specifically, perceived value and price consciousness will be tested as antecedents of attitudes towards e-deals. Attitudes towards e-deals, subjective norms, and perceived behavioural control are proposed to have strong influences upon purchase intention. The theory of planned behaviour (TPB) provides the theoretical underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 78 publications
4
43
0
5
Order By: Relevance
“…For this reason, consumers make an effort to learn about the green products, their ingredients, their impact on the environment, and their functionality (Laroche et al, 2001). Apart from that, consumers also share the knowledge they have about the products with their friends and thus, they learn more (Khare, 2014;Cheah et al, 2015). As a result of this learning process, consumers are able to understand the environmental benefits of green products, which results in developing a predilection towards these products (Cegarra-Navarro & Martinez, 2010).…”
Section: Green Product Experience (Gpe)mentioning
confidence: 99%
“…For this reason, consumers make an effort to learn about the green products, their ingredients, their impact on the environment, and their functionality (Laroche et al, 2001). Apart from that, consumers also share the knowledge they have about the products with their friends and thus, they learn more (Khare, 2014;Cheah et al, 2015). As a result of this learning process, consumers are able to understand the environmental benefits of green products, which results in developing a predilection towards these products (Cegarra-Navarro & Martinez, 2010).…”
Section: Green Product Experience (Gpe)mentioning
confidence: 99%
“…The results of other studies indicate that the most significant factors that influence consumer purchase intention are consumer attitudes and price perceptions (Jaafar et al, 2013). In line with these findings, the results of research on online promos show that attitudes and normative are affecting consumer purchase intentions (Cheah et al, 2015). Ali (2017) explained in his research on the purchase intention of halal products in Pakistan that attitudes have a positive influence on the purchase intention of halal food for non-Muslim consumers.…”
Section: Effect Of Attitude Toward Behavior On Purchase Intentionmentioning
confidence: 81%
“…Based on a theoretical study from Dwipayani and Rahyuda (2016), Jaafar et al (2013), Cheah et al (2015), Ali (2017) and Maichum et al (2017) hypotheses can be drawn as follows:…”
Section: Effect Of Attitude Toward Behavior On Purchase Intentionmentioning
confidence: 99%
“…If we refer to the research conducted by Thamizhvanan and Xavier (2013), Kim and Ahn (2007), Chen and Barnes (2007), Sun (2010), Pavlou and Gefen (2004), Hsu et al (2014), Shadkam (2012), Becerra and Korgaonkar (2011), Kim JB (2012), and Schlaegel (2015) has a similar suggestion to put the this two construct to the model to complete the missing factor. Perceived behavioural control is also mentioned in several papers regarding digital platform such as Cheah et al (2015) and Dakduk et al (2017) which is interesting to be concluded into this study.…”
Section: Introductionmentioning
confidence: 87%